(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2024)
An exceptionally abundant supply of significant chemicals with structurally unique and physiologically active metabolites may be found in the marine environment. Mangrove plants have long been utilized in traditional medicine to cure a variety of illnesses all around the globe. Very few efforts have been undertaken to test the validity of these claims in controlled trials, despite the fact that several mangroves and mangal companions are suggested in traditional medicine as being effective against a variety of ailments. Acanthus ilicifolius Linn, often known as sea holly (acanthaceae), is a salty plant that is typically found around the southeast coastlines of India. It is well-known for its wide range of secondary metabolites and its traditional uses. Using a Soxhlet apparatus, the leaves of Acanthus ilicifolius were gathered, shade-dried, ground into a coarse powder, defatted with petroleum ether, and then extracted with ethanol. Assessment of the effects of an ethanolic extract of Acanthus ilicifolius leaves as a central nervous system depressant. Mice were subjected to a number of behavioral tests, including the Tail Suspension Test (TST) and the Forced Swimming Test (FST). The immobility periods in the FST extract at dosages of 100, 250, and 500 mg/kg were considerably (P<0.0001) longer than those in the control group. When compared to a normal medication, TST considerably lengthens the immobility period when the dosage is increased. The drug’s interaction with the GABA ergic system may be the cause of these depressed patterns.